Efektivitas penggunaan metode cooperative learning type make a match terhadap pemecahan masalah siswa dalam pembelajaran matematika - Rita Rosita; Ricki Yuliardi; Abdul Rosyid (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2018)
Student problem solving on learning mathematics in Class X SMK YAMSIK Kuningan is still low. This is because the implementation of conventional learning model that less develop the ability to learn and build individuals. Conventional learning tends to minimize student involvement so teachers seem to be more active. The habit of being passive in the learning process can cause most students to be afraid and embarrassed to ask the teacher about the less interesting material. One of the learning models tried through this research is the Make A Match learning model. The purpose of this research is to know the effectiveness of Make A Match method in learning mathematics. The population of this research is students of class X SMK YAMSIK Kuningan. Sampling in this research using Cluster Random Sampling technique with M-G pattern that is using balancing technique average pretest value of control group and experiment group. There are 2 (two) variables in this research, namely: (1) Make A Match Learning Model with conventional learning model, and (2) Problem solving student. Data collection techniques used are documentation, tests, and questionnaires. Instrument test results (validity test, level of difficulty, distinguishing power) consisting of 5 items and used for pret test and post test are 5 items. Based on the results of instrument reliability test for pretest, postes, and questionnaires obtained the whole instrument is reliable and can be used for data collection. The test result difference of two average pret test (t is in the acceptance area of ​​Ho) concluded there is no difference between the experimental group and the control group. Test of difference of post experiment group average and control group was found that experimental group was better than control group. Average estimation in control group with mean of student learning result 35.92 meanwhile experimental group average estimation with mean of result of learning 37.94 mean control group result of problem solving at learning of mathematics lower than experiment group, hence there is influence between effectiveness The model of Make A Match learning in mathematics learning in grade X students of SMK YAMSIK Kuningan. Based on the results of the study concluded that learning by using Make A Match model socialized and used as an alternative in learning mathematics in school. In addition to further research as the development of other research. Based on the results of the study it is suggested that the application of Make A Match learning model is socialized and used as an alternative in learning mathematics in schools to improve student learning outcomes. In addition, in the application of this model a teacher should always keep an eye on the class to motivate students' activeness and provide individual and group guidance. Further research needs to be done as self-development so as to develop research in a wider scope.